Effect of Porosity in Catalyst Layers on Direct Methanol Fuel Cell Performances. Issue 2 (1st February 2013) - Lee, Y.; Kim, T. K.; Choi, Y. S.
Abstract Effects of porosity of catalyst layers (CLs) on direct methanol fuel cell (DMFC) performances are investigated using silicon dioxide (SiO2) particles as a pore former. The pore size and volume of CLs are controlled by changing the size and content of SiO2. As the size of pore formed by removal of SiO2 increases, DMFC performances are enhanced. The augmentation in performances can be explained by facilitation of fuel transport to catalyst particles, increase of utilization efficiency of catalysts, diminishment in methanol crossover, reduction in activation loss and facilitation of water discharging out of CLs of cathode due to the controlled porosity in CLs. The enhanced fuel transport, accessibility of fuels to Pt catalyst surface, is proved by the active areas of Pt catalyst. In addition to the active area of Pt catalyst, porous CLs exhibit a decline in methanol crossover, leading to increase of open circuit voltage (OCV). The porous CLs also show improvements in activation loss due to high porosity, causing enhancement in DMFC performances. In aspect of pore volume contribution to cathode performance, the SiO2 content is optimized. Based on the DMFC performances, it can be suggested that the optimum conditions of SiO2 are 500 nm in size and 20 wt.% in content. The porosity effect on both electrodes appears as follows: the pores in cathode are more effective on DMFC performances (55.5%) than those of anodes (44.5%) based on the maximum power of DMFC, indicating that the pores in CLs facilitate removal of water from electrodes.